2019
DOI: 10.1127/ejm/2019/0031-2885
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative decomposition products of synthetic NaFePO4 marićite: nano-textural and electrochemical characterization

Abstract: Single-phase marićite, NaFePO4, was synthesized from monosodium phosphate and iron oxalate at 750°C, at atmospheric pressure. Thermal treatment of synthetic marićite in air indicated oxidative decomposition into Na3Fe 3+ 2(PO4)3 nasicon and-Fe2O3 at temperatures above 225°C. Intergrowth of the reaction products is found to occur at the nanoscale without identified crystallographic relationship with the marićite precursor. Electrochemical activity of the reaction product is confirmed with the reversible inserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[53,54] The study of electrochemical activity in battery by 4D-STEM mapping was first reported by Kübel et al [55] in which the authors showed the statistical orientation information on the LiFePO 4 /FePO 4 interface in individual grains with phase mapping extracted from ASTAR data. Other similar works based on the mapping of crystalline phase and orientation mapping using 4D-STEM approach is reported by Su et al [56] and Brunet et al [57] The cross-section bright field TEM image of a pristine lamella is shown in Figure 4a. All layers are easily identified by contrast: Si substrate, Al 2 O 3 , Pt, LMNO thin film, and Pt protective coating.…”
Section: Study Of Pristine Fib-lamella Before Cyclingmentioning
confidence: 52%
“…[53,54] The study of electrochemical activity in battery by 4D-STEM mapping was first reported by Kübel et al [55] in which the authors showed the statistical orientation information on the LiFePO 4 /FePO 4 interface in individual grains with phase mapping extracted from ASTAR data. Other similar works based on the mapping of crystalline phase and orientation mapping using 4D-STEM approach is reported by Su et al [56] and Brunet et al [57] The cross-section bright field TEM image of a pristine lamella is shown in Figure 4a. All layers are easily identified by contrast: Si substrate, Al 2 O 3 , Pt, LMNO thin film, and Pt protective coating.…”
Section: Study Of Pristine Fib-lamella Before Cyclingmentioning
confidence: 52%